Analyzing opacity with contextual faithfulness constraints. Issue 1 (20th August 2020) - Hauser, Ivy; Hughto, Coral
Abstract : Phonological opacity is well-studied and there are numerous proposals in the literature which analyze opacity in Optimality-Theoretic grammars. However, many analyses include significant elaborations to the basic architecture of Optimality Theory (Prince & Smolensky 1993/2004 ) or its serial alternative, Harmonic Serialism (McCarthy 2000 ). In this paper, we propose a method of analyzing opacity which avoids additional significant enhancements to the basic theory by using faithfulness constraints with input-defined contexts. These constraints bear many similarities to standard positional faithfulness constraints (Beckman 1997 ; 1998 ; Lombardi 1999 ), but the context is input-defined (as in Jesney 2011 ). Adding context to faithfulness constraints has previously been discussed as a potential solution to counterfeeding opacity, but dismissed on account of potentially creating an overly rich faithfulness theory (McCarthy 2007a ). We argue that the analytical potential of these constraints outweighs the potential problems associated with overgeneration. We show that contextual faithfulness constraints can be employed to analyze multiple types of underapplication opacity in parallel OT and multiple types of under- and overapplication opacity in Harmonic Serialism. We discuss the impact of including these constraints in a universal CON and suggest the potential of language-specific constraint induction for mitigating over-generation effects.